Company Profile: Caprion Proteomics, Inc. (August 2009) - Chelsky, Daniel; LeBlanc, Martin
Caprion Proteomics, Inc. is a leading provider of proteomics biomarker services with over 20 pharmaceutical, biotechnology and diagnostics industry clients in North America, Europe and Japan. An unbiased approach to the identification of biomarker candidates is paired with a rapid tool for biomarker verification and validation in large patient populations. Caprion is now also a strategic partner of Covance, Inc., one of the world''s largest and most experienced providers of drug-development services.